Sitios utilizados por la nutria neotropical en una selva baja caducifolia en la costa de Oaxaca, México - Casariego-Madorell, Ma. Antonieta (THERYA, 2013)
This work was carried out in the river Copalita and Zimatán located in Huatulco within the municipalities of San Pedro Huamelula, Santiago Astata and San Miguel del Puerto in Oaxaca State. The samplings were carried out July 1999 to September 2000, identifying key areas for otters, such as resting sites and sites frequently used for sprainting. This was done by walking down the river banks, looking for any evidence of the presence of otters, such as footprints, food remains and scats, all of them were recorded. Two dens were found on Zimatán; this river was apparently preferred Copalita River, although no significant differences in frequency of use were found between these rivers. There were other organism recorded, such as raccoons, skunks, foxes, jaguaroundi, puma and jaguar. Results emphasizes the importance of protecting these areas, not only for the otter, but also for the others species that are found in this area. Key words: Dens, frequency of use, Neotropical otter, Oaxaca, scats.